Efferent and afferent connections of the ventromedial hypothalamic nucleus determined by neural tracer analysis: Implications for lordosis regulation in female rats. (February 2015) - Shimogawa, Yuji; Sakuma, Yasuo; Yamanouchi, Korehito
Highlights: Afferents and efferents of VMN were analyzed in female rat forebrain and midbrain. Retrograde or anterograde neural tracer, FG or PHA-L, was injected into the left VMN. Direct left and right neural connections of the ventrolateral VMN were observed. Connections between the left VMN and most nuclei were reciprocal. Left VMN sends axons bilaterally to most nuclei with dominance of ipsilateral fibers. Abstract: Neural connections of the ventromedial hypothalamic nucleus (VMN) to and from forebrain and midbrain structures, which are involved in the neuroendocrine regulation of reproduction, were investigated. A retrograde (fluoro-gold [FG]) or an anterograde neural tracer (phaseolus vulgaris-leucoagglutinin [PHA-L]) was injected into the left side of the VMN in ovariectomized rats. Six days after injection with FG or 11 days after injection with PHA-L, brains were fixed and sectioned. After immunohistochemistry, digital images of FG-labeled neural cell bodies (FG-cells) or PHA-L-labeled fibers (PHA-L-fibers) were analyzed. Injection sites of FG and PHA-L were mainly in the ventrolateral VMN. Considerable numbers of FG-cells and PHA-L-fibers were present in the left side of the medial amygdala, ventral lateral septum, preoptic area, bed nucleus of stria terminalis, dorsomedial hypothalamic nucleus, arcuate nucleus, periventricular nucleus of thalamus, and midbrain central gray. The lateral dorsal raphe nuclei contained many PHA-L-fibers but few FG-cells. By contrast, both sides of the median raphe nucleus contained many FG-cells but few PHA-L-fibers. Reciprocal direct neural connection between the right and left side of the VMN were observed. The present results provide an anatomical basis for functional relationships between the VMN and these nuclei.